Trend Analysis of the Link Between Tax Reveneue, Non-Tax Revenue and Public Expenditure in Nigeria - Emmanuel John Kaka (Universitas Syiah Kuala, 2020)
Objective – The paper is aimed at examining the relationship between government tax revenue, non-tax revenue and government expenditure in Nigeria. Design/methodology – Quantitative research design was employed. Secondary data were collected from Central Bank of Nigeria statistical bulletin, World Bank, World Data Atlas and Federal Inland Revenue Service. The study covers the period of 2010 to 2018. Meanwhile descriptive statistics was used to analyzed the data. Results – The findings of the study discovered that, there is a relationship between government revenue and government expenditure, and the Nigerian government revenue and expenditure is in line with the spend-and-revenue hypothesis. That is government revenue only respond to previous changes in expenditure. Thus, government is expected to generate enough tax revenue to enable it meet government expenses as revenue from oil is decreasing. This signifies that whenever there is high government expenditure, it is required that government must raise higher revenue, and in Nigeria, government expenditure is always higher than the revenue resulting to budget deficit. In addition, tax revenue was found to have been increasing even though at a slower rate. Limitation/Suggestion - The study recommends that Nigerian government should cut down current expenditures on wages, acquisition of goods and services that are unnecessary and increase capital expenditure. Increase in capital expenditures on education, infrastructures and health care will boast the economic activity and which will in turn increases government tax revenue.